Information behaviors and information literacy skills of LIS students: An international perspective - Saunders, L.; Kurbanoglu, S.; Boustany, J.; Dogan, G.; Becker, P.; Blumer, E.; Chowdhury, S.; Dobreva, M.; Gendina, N.; Hebrang Grgic, I.; Haddow, Gaby; Koltay, T.; et al. (Association for Library and Information Science Education, 2015)
Librarians are expected to be expert searchers, and developing information literacy skills to navigate the vast world of information is a focus of most library and information science (LIS) programs. It is important to understand the information literacy and behaviors of LIS students to see if they are employing the skills they will need to assist and educate their future patrons, yet there is relatively little research into the information literacy and behaviors of librarians and library students. Using a survey on information behaviors, this study addresses this gap in the literature by examining how LIS students in 18 countries search for, evaluate, and use information in various contexts, and on whom they rely for help. The results of this study demonstrate library science students' information literacy skills within an international context. Faculty in LIS programs will be interested to see how their students approach information problems, and might use this understanding to develop or strengthen courses and inform curricular decisions.